Support for the underrepresented sex: new descriptions of scutacarid males (Acari, Heterostigmatina) - Jagersbacher-Baumann, Julia; Ebermann, Ernst (Zootaxa, 2016)
Based on males gained from laboratory cultures, nine new descriptions and one redescription of scutacarid males are given: the respective species are Heterodispus foveatus Jagersbacher-Baumann and Ebermann 2012, Imparipes dispar Rack, 1964, Lamnacarus ornatus Balogh and Mahunka, 1963, Scutacarus acarorum (Goeze, 1780), S. deserticolus Mahunka, 1969, S. ellipticus Karafiat, 1959, S. longipes Rack, 1975, S. longitarsus (Berlese, 1905), S. tackei Willmann, 1942 and S. tyrrhenicus Ebermann, 1986. The taxonomic relevance of male morphology is evaluated. It reveals a strong potential for differentiating between species, and possible characters diagnostic for scutacarid genera are discussed. Within Heterostigmatina, males of Scutacaridae show the most derived characters.